Enhancing antitumor immunity via ROS-ERS and pyroptosis-induced immunogenic cell death in multiple myeloma - Rong Fu; Hao Wang; Chun Yang; Jia Song; Kai Ding; Liu Hui; Liu Zhaoyun; Xianghong Zhao (Journal for ImmunoTherapy of Cancer)
Background Few studies have focused on the development of multiple myeloma (MM)-specific immunotherapies. Tumor immunogenic cell death (ICD), triggered by damage-associated molecular patterns, may enhance MM-specific antitumor activity, offering a potential treatment strategy.Methods This study confirms that combining reactive oxygen species (ROS)-endoplasmic reticulum stress (ERS) and pyroptosis-inducers (ROS-ERS inducer 1 (REI) and Quillaja saponaria fraction 21 (QS-21), respectively) activates specific anti-MM immunity. MM cell lines were treated with REI and QS-21 alone or in combination and cytotoxicity and apoptosis were examined. ICD markers were identified, including calreticulin, ATP, heat shock protein 70, and high mobility group box 1. Additionally, changes in mitochondrial damage, endoplasmic reticulum stress, pyroptosis markers, and immune markers of dendritic cell (DC) maturation and T-cell activation were assessed both in vitro and in vivo.Results ROS-ERS combined with pyroptosis significantly induces MM cell apoptosis and enhances ICD marker activation. The combination treatment induces severe mitochondrial damage and endoplasmic reticulum stress, further promoting pyroptosis and MM-specific T-cell activation. In vivo, the combination treatment reduces tumor growth and improves DC and T-cell activation.Conclusions Thus, ROS-ERS inducers and pyroptosis inducers together significantly enhance the immunogenic response against MM, providing a promising strategy for MM treatment by activating powerful specific T-cell antitumor immunity.